2008
DOI: 10.1002/hbm.20703
|View full text |Cite
|
Sign up to set email alerts
|

White‐matter abnormalities in attention deficit hyperactivity disorder: A diffusion tensor imaging study

Abstract: Current evidence suggests that attention deficit hyperactivity disorder (ADHD) involves dysfunction in wide functional networks of brain areas associated with attention and cognition. This study examines the structural integrity of white-matter neural pathways, which underpin these functional networks, connecting fronto-striatal and fronto-parietal circuits, in children with ADHD. Fifteen right-handed 8 to 18-year-old males with ADHD-combined type and 15 right-handed, age, verbal, and performance IQ-matched, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
204
8
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(239 citation statements)
references
References 41 publications
22
204
8
5
Order By: Relevance
“…Makris et al (2008) showed that abnormalities of the cingulum bundle and superior longitudinal fascicle IIFconnection pathways that subserve attention and executive functionsFare evident in adults with ADHD. Lower corticospinal tract and superior longitudinal fasciculus FA (Hamilton et al, 2008) similarly suggested disruption of motor and attention networks in ADHD children, whereas the study by Silk et al (2008) indicated that fronto-striatal and fronto-parietal circuitry abnormalities exist in children with ADHD. Finally, pediatric samples showed decreased FA in the anterior corona radiata and abnormalities across multiple white matter tracts in ADHD, including the cingulum bundle, the superior and inferior longitudinal fasciculi, and internal capsule (Pavuluri et al, 2009).…”
Section: Selected Adhd Imaging Datamentioning
confidence: 99%
“…Makris et al (2008) showed that abnormalities of the cingulum bundle and superior longitudinal fascicle IIFconnection pathways that subserve attention and executive functionsFare evident in adults with ADHD. Lower corticospinal tract and superior longitudinal fasciculus FA (Hamilton et al, 2008) similarly suggested disruption of motor and attention networks in ADHD children, whereas the study by Silk et al (2008) indicated that fronto-striatal and fronto-parietal circuitry abnormalities exist in children with ADHD. Finally, pediatric samples showed decreased FA in the anterior corona radiata and abnormalities across multiple white matter tracts in ADHD, including the cingulum bundle, the superior and inferior longitudinal fasciculi, and internal capsule (Pavuluri et al, 2009).…”
Section: Selected Adhd Imaging Datamentioning
confidence: 99%
“…Tractography may reveal that these regions generally form a part of white-matter pathways connecting prefrontal and parieto-occipital areas with the striatum and cerebellum. Again, when the information both from fMRI and from DTI studies is evaluated together, it was found that in ADHD some cortical regions that have previously been shown is dysfunctional or hypoactive (Silk et al, 2009). In another study, it was suggested that alterations in brain white matter integrity occur in frontal and cerebellar regions in ADHD.…”
Section: Imaging Studies In Attention Deficit and Hyperactivity Disormentioning
confidence: 95%
“…Symptoms of stress closely match symptoms of ADHD Recent research sheds further light on the relationship between stress and ADHD. Vance, et al, demonstrated dysfunction of the right prefrontal regions of the brain in ADHD children [16]. This region is responsible for developing coping strategies, influencing the ability to handle stress.…”
Section: Memory Problems Forgetfulnessmentioning
confidence: 99%